Integrating an educational supply chain model in the higher education sector: meeting the 21st century workforce demands in Bangladesh - Chowdhury, Sabbir Ahmed; Sharmin, Rubaiya; Al- Amin, Md; Shifat, Md Nazmuzzaman (Frontiers in Education, 2025)
The higher education sector is facing challenges to meet the market demand of skilled workers in the era of the 4th Industrial Revolution (4IR). This study explores educational supply chain management systems in the higher education sector in Bangladesh. Qualitative data were collected through interview with stakeholders in educational supply chain management and analyzed to conceptualize a thematic framework for the educational supply chain. Findings of the study identify key skills required for developing a market-ready workforce and the ways to incorporate the skills in curriculum. The findings also illustrate the changes required in university culture, facilities and faculty capacity development at HEIs. The findings will guide policymakers, faculties, and relevant stakeholders to take strategic decisions about higher education supply chain management to create professionals aligned with the demand in the 21st century.